2007
DOI: 10.1002/tea.20208
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of algebraic and graphical thinking between mathematics and chemistry

Abstract: Students in undergraduate chemistry courses find, as a rule, topics with a strong mathematical basis difficult to master. In this study we investigate whether such mathematically related problems are due to deficiencies in their mathematics foundation or due to the complexity introduced by transfer of mathematics to a new scientific domain. In the investigation we exposed a group of students to a chemistry instrument based on the Nernst equation in electrochemistry, and an equivalent group of students to a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 38 publications
1
50
1
7
Order By: Relevance
“…Unlike the present study, much of the evidence found is primarily situated in the high school or undergraduate mathematics and science contexts (e.g. Brogt, Soutter, Masters, & Lawson, 2014;Bassok & Holyoak, 1989;Hoban et al, 2013;Marrongelle, 2004;Potgieter, Harding, & Engelbrecht, 2008). Frykholm and Glasson (2005) recognize the natural connections, relationships, and overlap between these two areas in the classroom and from their work, they determined that necessary training is needed for teachers to make strategic and deliberate integration of these two subjects.…”
Section: Connections and Cognitive Transfer Between Mathematics And Scontrasting
confidence: 55%
“…Unlike the present study, much of the evidence found is primarily situated in the high school or undergraduate mathematics and science contexts (e.g. Brogt, Soutter, Masters, & Lawson, 2014;Bassok & Holyoak, 1989;Hoban et al, 2013;Marrongelle, 2004;Potgieter, Harding, & Engelbrecht, 2008). Frykholm and Glasson (2005) recognize the natural connections, relationships, and overlap between these two areas in the classroom and from their work, they determined that necessary training is needed for teachers to make strategic and deliberate integration of these two subjects.…”
Section: Connections and Cognitive Transfer Between Mathematics And Scontrasting
confidence: 55%
“…Karam, 2014;Potgieter, Harding, & Engelbrecht, 2008;Rebello et al, 2007;Roorda, Goedhart, & Vos, 2015). This study extends the latter, but is different in the sense that it examines belief systems containing an organised set of mutually supportive beliefs (Borg, 2015;Mansour, 2009) about improving transfer of algebraic skills from mathematics into physics.…”
Section: Article Aim and Central Research Questionmentioning
confidence: 95%
“…This issue has been explored extensively in the literature on transfer and the role of context (Brown, Collins, & Duguid, 1989;Carpenter, 2012;Corte, 2012;Fischer, Bullock, Rotenberg, & Raya, 1993;Lave, 1993;McKeough & Lupart, 1995;Potgieter, Harding, & Engelbrecht, 2008;Rogoff, 1990;Salomon & Perkins, 1989;Willems, 2005). In our case students struggled to recognize whether Archimedes' principle was useful in a new context, and encountered difficulty in following their peers' reasoning as they described how they used the principle.…”
Section: Discussionmentioning
confidence: 83%